Role of clobetasol propionate 0.025% topical therapy in various dermatoses - Vishwanath, Vishalakshi; Chaudhary, Arvind; Agarwal, Ankit; Jyothi, Bhukya; Chitharanjan, C.; Bangady Killur, Lokesh Rao; Bhat, M. M.; Sarma, Nilendu; Palwade, Prashant K.; Banodkar, Pravin (International Journal of Research in Medical Sciences, 2021)
The anti-inflammatory and vasoconstrictive properties of topical corticosteroids (TCs) contribute in providing therapeutic benefits in several skin conditions, including atopic eczema, localized vitiligo, psoriasis, and chronic hand eczema. Clobetasol propionate (CP) is the most common topical agent used for psoriasis management and demonstrates an efficacy superior to other TCs. A new CP 0.025% cream formulation has demonstrated hypoallergenic effects due to the absence of known contact allergens, such as propylene glycol, short-chain alcohols, and sorbitol-based emulsifiers. Lower CP serum levels and less hypothalamic–pituitary–adrenal axis suppression with CP 0.025% cream formulation than with CP 0.05% ensure better safety. The present case series discusses the clinical experience of using CP 0.025% cream in various dermatological conditions.